Refinancing as a Proposal of Solution for Financial Problems in Companies Via Private Bank - Quiñonez Gutiérrez, Sebastián Alejandro (2018)
The objective of this research is to analyze refinancing as a solution to financial problems in companies with a private bank, in relation to their debts and to show a specific case of a company that has applied for refinancing. Information of a case from a company was made. When analyzing the financial problems that a company may face, which basically come from a low demand, financing is asked for, but when the company cannot pay the debt on the specified time, they will want to apply for refinancing by showing the bank that refinancing is an ideal option for the solution of their problem if they are taken into consideration with time and if cost-benefit is considered even without the necessity of making it with the same bank